Legal Review Of Fixed-Term Employment Agreements: Justice For Foreign Workers In Indonesia - Tajuddin Noor; Suhaila Zulkifli; Marlina Elisabeth pakpahan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
TThis study critically examines the legal framework governing Specific Time Work Agreements (Perjanjian Kerja Waktu Tertentu/PKWT) and the protection mechanisms afforded to foreign workers (Tenaga Kerja Asing/TKA) in Indonesia. As foreign direct investment continues to expand, particularly in strategic sectors such as construction, infrastructure, and information technology, the deployment of TKA has become increasingly prominent. However, the implementation of PKWT for foreign workers raises significant legal and human rights concerns, including ambiguity in contractual terms, unequal treatment, and insufficient safeguards for basic labor rights. Utilizing a normative juridical approach, this research analyzes existing statutes, legal doctrines, and regulatory practices to evaluate the extent of legal protections for TKA under PKWT arrangements. The findings reveal gaps between regulatory intent and implementation, underscoring the need for stronger institutional oversight, improved regulatory clarity, and enhanced legal literacy among both employers and foreign workers. The study concludes by emphasizing the importance of coordinated efforts between government authorities, private sector stakeholders, and legal institutions to establish a more equitable, transparent, and sustainable labor environment for foreign workers in Indonesia.